N × N Reconfigurable Nonblocking Polymer/Silica Hybrid Planar Optical Switch Matrix Based on Total-Internal-Reflection Effect - L. Liang; K. Zhang; C. T. Zheng; X. Zhang; L. Qin; Y. Q. Ning; D. M. Zhang; L. J. Wang (IEEE Photonics Journal, 2017)
We present a reconfigurable model for N × N non-blocking optical switch matrix (OSM) constituted by N(N-1)/2 2 × 2 thermo-optic polymer/silica hybrid total-internal-reflection switch elements. The number of the elements in the general model is reduced by about 50% compared to the reported all nonblocking OSM, in addition, the proposed model is more compact in footprint and more power-efficient. Each element consists of crossed multimode polymer/silica hybrid waveguides and a heater electrode at the switching node. A switching power of 53.9 mW is required at 1550-nm wavelength to drop the crosstalk below −28.0 dB. Measurements result in a rise time of 421.5/410.1 μs (O1/O2), a fall time of 534.2/464.6 μs (O1 /O2), and crosstalk of −27.6 and −29.1 dB under cross state and bar state, respectively. Subtracting coupling losses, propagation losses of the device under cross state and bar state are about 1.0 and 1.8 dB, respectively. The fabricated 3 × 3 and 4 × 4 reconfigurable non-blocking OSMs using three and six switch elements at sizes of 16.0 mm × 6.8 mm and 26.0 mm × 6.8 mm all show excellent switching performances, and the insertion losses are less than 3.6 and 7.2 dB, respectively.